"Freedom of speech requires actions": Exploring the discourse of politicians convicted of hate‐speech against Muslims. (14th March 2019) - Pettersson, Katarina
Abstract: This study explores how politicians convicted of hate‐speech against Muslims account for their actions in statements on their Facebook‐pages as well as in reported interviews. Taking a critical discursive psychological perspective, the study examines the strategies through which the politicians discursively claim and resist various subject positions, thus managing to construct their hate‐speech as everything from trivial mishaps to acts of virtue. The study examines the multifaceted dynamics of these constructions, and shows how elements from the Five Step Social Identity Model of the Development of Collective Hate are flexibly deployed in the discourse to serve distinct social and political purposes. By allowing the Social Identity and (critical) discursive approaches to challenge and develop each other, the study advances social psychological research on political communication and persuasion, and contributes to the debate on the boundaries between hate‐speech and freedom of speech.